Analysis of Moral Messages in the Short Movie “Aku dan Mesin Waktu” by Upie Guava - Roskha, Berliana Nanda; Prathisara, Gibbran (International Journal of Science and Society, 2025)
The purpose of this study is to describe the moral message related to relationships with others and relationships with oneself contained in the short movie Aku dan Mesin Waktu by Upie Guava. The study uses Roland Barthes' semiotic theory approach which will describe the analysis of the moral message contained in the film Aku dan Mesin Waktu. Qualitative research using Roland Barthes' semiotic theory. The data source is in the form of scenes in the film Aku dan Mesin Waktu. The data collection technique uses listening, reading, and taking notes. The data analysis technique uses qualitative descriptive. The results of the presentation show that several signs are found in the film Aku dan Mesin Waktu through various forms of visualized scenes, dialogues spoken, film settings, or shooting techniques. The study of semiotics brings up the denotative meaning, namely as the scene is displayed and captured by the audience by seeing the movements, expressions, dialogues carried out by the actors, and the situation of the scene. The connotative meaning, namely the intention of the message to be conveyed in the film hidden from the scenes shown, requires in-depth analysis. Myth is a way of conveying signs to interpret the message of each scene. The results of the semiotic analysis through the study of meaning in the form of a moral message from each scene that represents the reality of human life. Good moral messages can be examples and role models for positive behavior in films. Moral messages that show bad behavior from the actors can be advice and lessons for film lovers.